The Local Knowledge of Medicinal Plants by The Tanjung Merpati Village Community for The Postpartum and Infant Care - Yeni Mariani; Fathul Yusro; Evy Wardenaar; Yuliati Indrayani (Jurnal Biologi Tropis, 2022)
Women often experience various health problems with their reproductive organs. They also have to take several treatments during postpartum and infant care. In the community, these treatments generally use medicinal plants and become local knowledge. This study aimed to document the local knowledge of Tanjung Merpati Village community in using medicinal plants for postpartum and infant care. We interviewed a total of 96 respondents, who are the general public in Tanjung Merpati Village. The data obtained were analyzed in the form of use-value (UV), informant consensus factor (ICF), and fidelity level (FL). The analysis results showed 22 species of medicinal plants used for postpartum and infant care. Plants such as kunyit kuning (Curcuma longa), cokur (Kaemperia galanga), entomu (Curcuma xanthorriza), and ginger (Zingiber officinale) have the highest UV values with values respectively (1; 0.96; 0.84 and 0.8). Baby haircare shows the highest ICF value. Several plants have the highest FL value (100), namely manjakani (Quercus infectoria) and asam kanis (Garcinia xanthochymus) (postnatal maternal care), ayau (Litsea sp) (baby poultice), kumis kucing (Orthosiphon aristatus), and coconut (Cocos nucifera) (fever in infants), jackfruit (Artocarpus heterophyllus) (treatment of baby's umbilical wound), lidah buaya (Aloe vera) (baby haircare), mengkudu (Morinda citrifolia) (stomachache and bloating in infants), as well as pisang (Musa sp) and cangkok manis (Sauropus androgynus) (enhance mother breast milk). Conclusions from the results of the study indicate that the people of Tanjung Merpati Village have local knowledge regarding postpartum and infant care, and this knowledge is still well maintained in the community.